The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1403656
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bipolar vs. tripolar concentric ring electrode Laplacian estimates

Abstract: Potentials on the body surface from the heart are of a spatial and temporal function. The 12-lead electrocardiogram (ECG) provides useful global temporal assessment, but it yields limited spatial information due to the smoothing effect caused by the volume conductor. The smoothing complicates identification of multiple simultaneous bioelectrical events. In an attempt to circumvent the smoothing problem, some researchers used a five-point method (FPM) to numerically estimate the analytical solution of the Lapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…On the other hand, one of the main limitations of surface bioelectric recording by means of conventional disc electrodes is the poor spatial resolution, mainly originating from the blurring effect due to different conductivities of the body volume conductor [ 23 , 24 ]. To overcome this limitation, surface Laplacian potential records have been proposed [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, one of the main limitations of surface bioelectric recording by means of conventional disc electrodes is the poor spatial resolution, mainly originating from the blurring effect due to different conductivities of the body volume conductor [ 23 , 24 ]. To overcome this limitation, surface Laplacian potential records have been proposed [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, surface Laplacian potential records have been proposed [ 25 ]. Literature has confirmed that Laplacian records are able to mitigate this effect and provide enhanced spatial resolution surface potential recordings—i.e., they are able to improve the detection of the bioelectric dipole sources closest to the recording electrodes, rejecting the contribution of distant bioelectric dipole sources—when compared to bipolar records made with disk electrodes [ 24 ]. First, surface Laplacian potentials were estimated using monopolar disc electrodes and applying discretization techniques [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The non-invasive recording of electrophysiological signals is commonly used in several fields of applied medicine, such as electrocardiography, electroencephalography and electromyography of many other organs and muscles. Although these recordings are usually made with conventional disc electrodes, these yield poor spatial resolution, caused in part by the blurring effect of the different conductivities of the volume conductor [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tripolar recording configuration is more spatially sensitive with a smaller amplitude than the bipolar. When signal amplitude is more important than spatial specificity, then the bipolar configuration appears superior [ 2 , 8 ]. Regarding electrode dimensions, it is known that the larger the electrode the wider the recording area, the deeper the sources that can be sensed and the higher the signal amplitude, but also the poorer the spatial selectivity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The space between the electrode elements is insulated and the radial distance between the insulated areas is equal. Suppose the center plate is a dot and the radius of the two concentric rings are r and 2r separately, the surface Laplacian of the sensor is [6] ) ) , 2 ( 2 . SIGNAL CONDITIONING…”
Section: Introductionmentioning
confidence: 99%